2018
DOI: 10.3126/ajms.v9i6.21059
|View full text |Cite
|
Sign up to set email alerts
|

Genitourinary fistulas experience in a tertiary hospital in North-Western Nigeria

Abstract: Background: Genitourinary fistulas are devastating, with obstetric fistula being the most common type and a major public health problem in the developing world.Aims and Objectives: This study was designed with an aim to determine the epidemiology of genitourinary fistulas in our centre.Materials and Methods: A 5 year (1st January 2013 to 31st December 2017) retrospective review based on data extracted from the case files of patients managed for gynecological fistulas at the Usmanu Danfodiyo University Teaching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
2
4
0
Order By: Relevance
“…Fistula surgery is a delicate procedure and success rate is reduced with each successive attempt. This finding is consistent with other study 22 . In literature 93% success rate of VVF is seen in patients who did not have any previous attempts of repair 26 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Fistula surgery is a delicate procedure and success rate is reduced with each successive attempt. This finding is consistent with other study 22 . In literature 93% success rate of VVF is seen in patients who did not have any previous attempts of repair 26 .…”
Section: Discussionsupporting
confidence: 94%
“…Other studies showed similar findings. Vesico-vaginal fistula was the most common type among all genitourinary fistulae accounting for 64-78% in various studies 20,21,22 .In our study the second most common type was uretero-vaginal fistula accounting for 10% of all varieties. Similar incidence was found in other study 20 .Priyadarshi et al quoted the frequency of uretero-vaginal fistula as 14% 21 .…”
Section: Discussionsupporting
confidence: 52%
“…These studies were all conducted in public secondary and tertiary hospitals with the sample population ranging from doctors and nurses to patients. The risk of bias in the studies were low risk for two studies[20,21], some concern for one study [22], and high risk for two studies[23,24]. The search details are shown in Table 1 with the summary of included studies shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…One study examined the impact of EMR on patient care and satisfaction [23]. The study had a cross-sectional design and was conducted among 300 patients at the Federal Medical Centre, Keffi, Niger State, with the aim of assessing patients' satisfaction with EMR implementation at the hospital's pharmacy.…”
Section: Patient Care and Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation